2004
DOI: 10.1161/01.cir.0000143893.18451.0e
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial Stenosis Severity Does Not Affect Minimal Microcirculatory Resistance

Abstract: Background-Whether minimal microvascular resistance of the myocardium is affected by the presence of an epicardial stenosis is controversial. Recently, an index of microcirculatory resistance (IMR) was developed that is based on combined measurements of distal coronary pressure and thermodilution-derived mean transit time. In normal coronary arteries, IMR correlates well with true microvascular resistance. However, to be applicable in the case of an epicardial stenosis, IMR should account for collateral flow. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
178
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 221 publications
(187 citation statements)
references
References 21 publications
5
178
2
Order By: Relevance
“…[1][2][3] We have found that it correlates well with an accepted experimental technique for determining microvascular resistance 1 and that it is more reproducible than CFR. 14 The ability to assess easily and accurately both the epicardial artery and the microvasculature simultaneously by measuring FFR and IMR with a single wire is a potential advantage over the standard methods of using IVUS and a Doppler velocity wire.…”
Section: Author Manuscriptmentioning
confidence: 61%
See 1 more Smart Citation
“…[1][2][3] We have found that it correlates well with an accepted experimental technique for determining microvascular resistance 1 and that it is more reproducible than CFR. 14 The ability to assess easily and accurately both the epicardial artery and the microvasculature simultaneously by measuring FFR and IMR with a single wire is a potential advantage over the standard methods of using IVUS and a Doppler velocity wire.…”
Section: Author Manuscriptmentioning
confidence: 61%
“…[1][2][3] The purpose of this study is to Correspondence Address: William F. Fearon, M.D., Center for Research in Cardiovascular Interventions, 300 Pasteur Drive, Room H3554, Stanford University Medical Center, Stanford, wfearon@stanford.edu. Publisher's Disclaimer: This is a PDF file of an unedited manuscript that has been accepted for publication.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 It has been demonstrated that IMR correlates very well with true microvascular resistance and can distinguish between normal and abnormal microcirculatory function without being influenced by the presence of epicardial arterial stenosis. 6 In addition, Fearon demonstrated that, compared to other traditional methods for assessing the microvasculature, IMR appears to be a better predictor of microvascular damage and recovery of left ven-ITO N et al tricular function after ST-segment elevation MI (STEMI). 7 Although microvascular injury following PCI can be evaluated with IMR, no method of treatment has been established.…”
mentioning
confidence: 99%
“…1) An increased microcirculatory resistance indicates the presence of coronary microvascular dysfunction (CMVD), a term introduced to describe abnormalities in the regulation of microvascular blood flow. CMVD has been found to play an important role in determining ischemic threshold 2) and to be independent of epicardial stenosis severity. 3) Smoking is known to be associated with the development of epicardial atherosclerosis and impairment of coronary endothelial function.…”
mentioning
confidence: 99%